2020
DOI: 10.1177/2158244020924377
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Pain and the Quality of Postoperative Pain Management in Surgical Patients

Abstract: The aim of the study was to investigate surgical patients’ pain experience and the quality of nursing care in managing acute postoperative pain. A descriptive cross-sectional study using a Strategic and Clinical Quality Indicators in Postoperative Pain Management Questionnaire collected data of 247 patients who underwent surgery in the surgical clinics of a state hospital. Data of 141 patients were included in the analysis. The mean scores for the scale items indicated that the quality of care was acceptable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In this study, patients who received pain treatment within 10 minutes reported that their pain severity did not decrease, and their first night of sleep was negatively affected by pain. In one study, the patients reported medium and severe pain even though more than half of the patients were treated quickly, similar to our findings (Köse Tamer & Sucu Dağ, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, patients who received pain treatment within 10 minutes reported that their pain severity did not decrease, and their first night of sleep was negatively affected by pain. In one study, the patients reported medium and severe pain even though more than half of the patients were treated quickly, similar to our findings (Köse Tamer & Sucu Dağ, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…This association is concerning, as many surgical patients experience under-managed pain ( Willingham et al., 2021 ). In one study of 247 surgical patients, more than half suffered with severe pain on the first post-operative day ( Köse Tamer and Sucu Dağ, 2020 ). Reports of moderate to severe post-operative pain are supported throughout the literature ( Öğüt and Sucu Dağ, 2019 ; Werner and Kongsgaard, 2014 ; Zoëga, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…High levels of pain in post-operative patients have been reported to contribute to negative expectations and anxiety ( Dagyaran et al., 2021 ; Henningsen et al., 2018 ; Köse Tamer and Sucu Dağ, 2020 ). For example, patients who had expectations of high pain intensity or inadequate relief due to prior pain experiences were five times more likely to report increased anxiety when compared to patients whose pain was previously well-managed ( Egan et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported improved pain relief and reduced opioid requirements with the combination of bupivacaine and morphine [24] [25] [26], while others have reported no significant differences in analgesic efficacy compared to bupivacaine alone. Poor monitoring, delayed response to patient's pain, and inaccurate pain score contributes to the challenge that is still faced in postoperative pain treatment [27]. There is however a paucity of studies regarding postoperative pain management despite the increasing number of surgical cases over the years in Ghana and Africa [28].…”
Section: Introductionmentioning
confidence: 99%